Fever awareness, management practices and their correlates among parents of under five children in urban India - Thota, Sanjana; Ladiwala, Nida; Sharma, Pawan Kumar; Ganguly, Enakshi (International Journal of Contemporary Pediatrics, 2018)
Background: Awareness regarding fever is reportedly low among Indian urban parents, leading to its over- management among under five children. We attempted to study the awareness and fever management practices of South Indian urban parents. The objectives were to find the awareness of parents regarding childhood fever management, and correlates of practices. Methods: One hundred parents of under-five children with history of fever in past three months were randomly selected and interviewed using a predesigned tool. Children’s weight and height was measured. Awareness scores for causes of fever and fever management were constructed. Logistic regression was done to identify correlates of incorrect practices. Results: 95% parents were aware about correct temperature above which fever became harmful. Awareness score for causes of fever was poor (<1) among 41% parents. Mothers’ complications awareness scores were better than fathers (p<0.05). 81% parents used antibiotics; only 18% consulted a doctor before doing so. 17% parents using antibiotics did not complete the prescribed course. The independent correlates of poor fever management practices were working parents (OR: 6.28; 95%CI: 1.7-23.16), lesser number of children (OR: 3.08; 95%CI: 1.01-9.37), poor compliance for antipyretics (OR: 9.20; 95%CI: 1.64-51.52) and giving antipyretics without consulting doctors (OR: 5.43; 95%CI: 1.69-17.47). Poor knowledge of available pediatric antipyretic preparations was negatively correlated (OR: 0.13; 95%CI: 0.02-0.64). Conclusion: Fever awareness was fair among urban parents. Mothers had better awareness than fathers. Increased awareness for correct fever management of under-five children is desirable among urban parents to reduce misuse of antibiotics and antipyretics.